PENGARUH PENGEMBANGAN KARIR, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK RIAU KEPRI KANTOR PUSAT PEKANBARU - Siti Khuzaimah; Restu '; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the influence of career development, competence, and work environment partially or simultaneously on the job satisfaction employeesat pt. bank riau kepri head office pekanbaru. The population in this study were all employees totaling 276 employees and 73 employees were sampled by using the formula slovin, using instrumental testing the validity, reliability and classic assumption test. The analytical method used in this study is descriptive analysis and multiple linear regression analysis using SPSS 21 for windows. From the results of the testing that has been done, simultane ous regression test (F-test) showed that the variables of career development, competence and workenvironment simultaneously significant effecton job satisfaction employees. And the results ofthe partial test (t test) showedthat thevariablesof job career development, competence and work environment partially significant effecton job satisfaction employees. The result of the calculation of the coefficient of determination (R2) is equal to 0,779, which means, career development, competence, and work environmentjointly affect the job satisfaction employees amounted to 77.9%, while the remaining 22.1% is influenced by other variablesthat no tex amined inthis study.Keywords : Career Development, Competence, Work Environment, and Job Satisfaction Employees.